Analisis Pengelolaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) Terhadap Peningkatan Pendapatan Asli Daerah - Amelia Ramadayanti; Arry Irawan; Jouzar Farouq Ishak (Indonesian Accounting Research Journal, 2022)
This research aims to analyze the management of PBB-P2 carried out by the local government of West Bandung Regency to increase PAD and what factors can affect the management of PBB-P2. This research uses qualitative research methods using Nvivo 12 Plus Software. The technique of collecting data are carried out by conducting interviews. The results indicate that West Bandung Regency Government has complied with the Regent's Regulation Number 19 of 2019. This research was found that the implementation of PBB-P2 management includes planning, implementation and supervision which have been carried out with the regulations and with optimal management of PBB-P2 can help to increase PAD revenus in the West Bandung Regency Government. In carrying out the management of PBB-P2 there are factors that influence the management to be not optimal there are NJOP, taxpayer awareness, Human Resources (HR), economic and database.